2003
DOI: 10.1093/nar/gkg406
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of mouse DNA methyltransferase 1 (Dnmt1) is regulated by both E2F-Rb-HDAC-dependent and -independent pathways

Abstract: Abnormal expression of Dnmt1 in vivo induces cellular alterations such as transformation, and an increase in Dnmt1 mRNA plays a causal role in c-fos-, ras- and SV40 large T antigen-induced transformation of fibroblasts in vitro. Here, we have investigated the regulation of Dnmt1 transcription. We identified the promoter region and major transcription start sites of mouse Dnmt1 and found two important cis-elements within the core promoter region. One is an E2F binding site, and the other is a binding site for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 57 publications
4
66
1
Order By: Relevance
“…For example, viral infection activates DNMT1 through the RB pathway (32). The DNMT1 promoter has been found to contain E2F-binding sites that are required for RB/E2F regulation in murine epithelial and human osterosarcoma cells (33,34). In our previous study, the DNMT1 and DNMT3A proteins were found to be overexpressed in NSCLC in a coordinate manner (11), suggesting a common regulatory pathway for expression of DNMT genes.…”
Section: Discussionmentioning
confidence: 95%
“…For example, viral infection activates DNMT1 through the RB pathway (32). The DNMT1 promoter has been found to contain E2F-binding sites that are required for RB/E2F regulation in murine epithelial and human osterosarcoma cells (33,34). In our previous study, the DNMT1 and DNMT3A proteins were found to be overexpressed in NSCLC in a coordinate manner (11), suggesting a common regulatory pathway for expression of DNMT genes.…”
Section: Discussionmentioning
confidence: 95%
“…A previous study has shown that the murine Dnmt1 gene contains two important cis-elements within the core promoter region (Kimura et al, 2003). One is an E2F binding site, and the other is a binding site for an unknown factor.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which these two proteins mutually control their expression is not yet investigated. However, an inhibition of DNMT1 expression by pRB is not excluded since ICBP90 increases the expression of this latter and that DNMT1 can be downregulated through the formation of E2F-pRB complexes (Kimura et al, 2003;McCabe et al, 2005). Such inhibitory effect could not occur in HTVs-SM1 cells probably because they have inactivated pRB.…”
Section: Icbp90 Interacts With Dnmt1 and Regulates Vegf Expression M mentioning
confidence: 99%